2015
DOI: 10.1007/s00264-015-2916-2
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder prosthesis in patients with rheumatoid arthritis: a systematic review

Abstract: RSA implanted in RA patients would appear to give similar results to those obtained in massive cuff tears with or without arthropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 54 publications
1
9
1
1
Order By: Relevance
“…11 For this reason, interest in the reverse TSA for the RA patient population has increased since its introduction in the US in 2004; 16 in fact, in RA patients with endstage inflammatory arthropathy and a damaged rotator cuff, the reverse TSA has demonstrated excellent results. [17][18][19][20] Based upon this evidence, it is not surprising that we found an exponential rise in the use of the reverse TSA since 2010, which corresponds to the introduction of an ICD-9 code for this implant. 21 Prior to 2010, it is likely that many implanted reverse TSAs were coded as TSA, and for this reason, we believe that the observed rise in the utilization of TSA in RA patients prior to 2010 may have been partly fueled by an increase in the use of the reverse TSA.…”
Section: Discussionmentioning
confidence: 64%
“…11 For this reason, interest in the reverse TSA for the RA patient population has increased since its introduction in the US in 2004; 16 in fact, in RA patients with endstage inflammatory arthropathy and a damaged rotator cuff, the reverse TSA has demonstrated excellent results. [17][18][19][20] Based upon this evidence, it is not surprising that we found an exponential rise in the use of the reverse TSA since 2010, which corresponds to the introduction of an ICD-9 code for this implant. 21 Prior to 2010, it is likely that many implanted reverse TSAs were coded as TSA, and for this reason, we believe that the observed rise in the utilization of TSA in RA patients prior to 2010 may have been partly fueled by an increase in the use of the reverse TSA.…”
Section: Discussionmentioning
confidence: 64%
“… 28 29) One was based on the only 5 studies that met their inclusion criteria. 28) The other included 7 studies for critical appraisal and data extraction as in our study. However, there were some differences in the method to analyze the results.…”
Section: Discussionmentioning
confidence: 99%
“…To address rotator cuff dysfunction, RSA has been used to treat shoulder destruction associated with RA in recent years. Good clinical outcomes fueled a significant increase in the number of RSA compared with the inevitable decrease of knee and hip arthroplasty utilization in RA patients as a result of revolutionary improvement in medication therapy 11,12 . In a recent study, Leroux et al 13 conducted a population-based investigation using Nationwide Inpatient Sample and found a significant increasing trend of utilization of shoulder arthroplasty in RA patients in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review, Cho et al 12 searched the literature from 1987 to 2014 and only found seven relevant studies, all with small sample that varied from eight to 27 cases. Furthermore, surgical complications such as prosthetic joint infection (PJI) and periprosthetic fracture are more common in RA patients compared with other indications due to poor bone and soft tissue conditions, and use of immunosuppressive drugs 11,15 . A meta-analysis indicated that the risk of PJI in patients with RA was significantly higher than that in patients with osteoarthritis 16 .…”
Section: Introductionmentioning
confidence: 99%